Evaluating the Uses of Concrete Demolishing Waste in improving the Geotechnical Properties of Expansive Soil - Safin B. Saeed; Kamal Ahmad Rashed (Journal of Engineering, 2020)
Expansive soil is one of the most serious problems that face engineers during the execution of any infrastructure projects. Soil stabilization using chemical admixture is one of the most traditional and widespread methods of soil improvement. Nevertheless, soil improvement on site is one of the most economical solutions for many engineering applications. Using construction and demolishing waste in soil stabilization is still under research., The aim of this study is to identify the effect of using concrete demolishing waste (CDW) in soil stabilization. Serious tests were conducted to investigate the changes in the geotechnical properties of the natural soil stabilized with CDW. From the results, it is concluded that the swelling potential of the expansive soil reduced and dramatic increases in unconfined compressive strength (UCS) value up to 3 times of its original value was reported. The results indicate that CDW is an economical solution to be used in soil stabilization whereas it is a sustainable idea to recycle constructional wastes and solve the continued need for the more landfilling area.